FORMATION OF SELF-ORGANIZATION OF EDUCATIONAL ACTIVITY OF STUDENTS OF HIGHER EDUCATION INSTITUTIONS (Pedagogy of Higher and Secondary Education, 2022)
In the article the basic of forming of self organization of studying activities of the students in the universities is considered.
Keywords: self-organization of studying activities of students; pedagogical reflextion; professional level; self-management